Persepsi Aktivitas Seksualitas Pada Masa Kehamilan Bagi Primipara Di Wilayah Kerja Puskesmas Wundulako Kabupaten Kolaka - Nurmitasari, Nurmitasari; Kurnaesih, Een; Idris, Arman (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2019)
Decreasing of sexual desire can be aproblem and contribute to the occurrence of stress and anxiety that can interfere with maternal and fetal health. The purpose of this research is to explore and analyze informants in depth about the perception of sexual activity during pregnancy for primipara based on physical conditions andp physchological conditios.This research used is qualitative research phenomenology approach with descriptive with primary data collection echique through indepth interview as many as 10 informants in primipara pregnant female about perception of their sexual activity during pregnancy. The result showed that the pregnant female feel pain in the intimate and swelling of the breast, the mouth feels bitter and belly bulge, while physic changes such as fear and anxiety to have sex and worried about the fetus that is contained so as that pregnant primiparas has sexual activity decreased sexual desire caused by physical andphysicologycal changes during pregnancy